RECOMMENDATIONS FOR THE APPLICATION OF TRAINING FORMS AND METHODS IN MOUNTAINEERING DURING THE PREPARATION FOR PERFORMING COMBAT TASKS BY SPECIAL PURPOSE UNITS - Khalep, Volodymyr (Honor and Law, 2023)
The article examines the forms and methods of training the technique of movement and insurance in the mountains, which can help servicemen of special purpose units during preparation for operations in mountainous terrain. The basis of the training of the above-mentioned units is mountaineering (altitude) training. It is important that at the current stage in the practice of mountaineering, there are a large number of different forms and methods of learning how to move on different forms of mountain terrain. Each of them is designed for certain requirements. But, as a rule, there are no methods that are universal or suitable for use in any conditions. Each method of movement is performed using a number of movements (elements). In mountaineering, two forms of training are used ‒ collective and group. Collective forms include traditional conversations and lectures using technical teaching aids. This is an introductory instructor and an annotated demonstration of technical techniques for students. In principle, this form allows you to achieve only the level of knowledge, but not skills. The latter requires cyclical training. Simply put, the instructor's check of knowledge acquisition by each learner and correction of errors. A large place during the training of climbers in a group form is occupied by practical classes, namely the work of the instructor with the department. Here there is an important opportunity to achieve mastery of the subject by each student at the level of skill. Skill is the conscious performance of a new action, that is, performance under the control of consciousness. A sign that the skill has been achieved is the quality of the action, its execution without errors. Skills are acquired through practical practice of new actions under the guidance of an instructor who makes timely corrections and helps to correct mistakes to each learner. In the "Curriculum for the training of climbers" a group form is provided for most of the practical classes. A particularly favorable situation ‒ training in a small group (5 people) is provided for the acquisition of skills by the trainees: the instructor simultaneously sees the actions of all his wards and can notice and correct all the mistakes of the trainees. As you know, a person can observe 7+2 objects. According to the current norms, there are 10 climbers in the "novice" division, so the instructor, even the most experienced, simply does not see one participant. The situation is very unfavorable. Taking into account the above, forms and methods of training units have been developed, as well as recommendations for their use with the aim of uniform training for the performance of tasks by military personnel of special purpose units in the mountains. The developed recommendations provide an opportunity for a uniform understanding of the training process, which in turn will ensure both higher quality training and a higher level of coordination of actions of special purpose units when performing tasks in the mountains.